2017
DOI: 10.5152/eurasianjmed.2017.17147
|View full text |Cite
|
Sign up to set email alerts
|

Global Alert: Zika Virus-an Emerging Arbovirus

Abstract: Zika virus (ZIKV) is an arbovirus of the Flavivirus genus, and it has an envelope and a single RNA molecule. In early 2016, the World Health Organization declared ZIKV infection to be an emerging global health threat. The major transmission route of the virus to humans is Aedes mosquitoes. ZIKV can be transmitted between humans by transplacental, perinatal, and sexual routes and via blood and body fluids. ZIKV infection usually results in a mild and self-limiting disease with low-grade fever, conjunctivitis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…However, the recent emergence and spread of ZIKV in the Americas has resulted in the WHO declaration of Public Health Emergency of International Concern, on 1 st February, 2016 due to the potential association between the infection and prenatal microcephaly or other brain anomalies. 3,5 Recent studies have suggested ZIKV infections to be highly neurotrophic, with a few cases reporting association with bilateral macular and perimacular lesions in eye. Guillain-Barré syndrome (GBS) was associated with the Zika virus outbreaks in Brazil and Venezuela.…”
Section: Epidimologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the recent emergence and spread of ZIKV in the Americas has resulted in the WHO declaration of Public Health Emergency of International Concern, on 1 st February, 2016 due to the potential association between the infection and prenatal microcephaly or other brain anomalies. 3,5 Recent studies have suggested ZIKV infections to be highly neurotrophic, with a few cases reporting association with bilateral macular and perimacular lesions in eye. Guillain-Barré syndrome (GBS) was associated with the Zika virus outbreaks in Brazil and Venezuela.…”
Section: Epidimologymentioning
confidence: 99%
“…Evidence implies transplacental transmission and perinatal transmission during delivery, with Zika virus RNA being found in amniotic fluid and in paired blood samples taken from newborn infants and mother. 5,6 Presentation, diagnosis and management From the obstetrician view point any maculo-papular rash with fever >37.2 o C occurring in pregnancy with conjuctivitis, myalgia, headache, pruritus, malaise or arthalgia should be thought as viral infection in endemic regions. Adverse outcomes have been noted regardless of the trimester during which the women were infected with ZIKV (55% of pregnancies had adverse outcomes after maternal infection in the first trimester, 52% after infection in the second trimester, and 29% after infection in third trimester.…”
Section: Epidimologymentioning
confidence: 99%
“…The virus has two lines: African and Asian. The virus of the American continent originated from the Asian lineage (Haddow et al, 2016;Ozkurt;Tanriverdi, 2017). V.2, N. 3.…”
Section: Introductionmentioning
confidence: 99%
“…Frank et al , Et al., 2014). In addition, the virus can resist up to 115 days in vaginal secretions and semen (Ozkurt;Tanriverdi, 2017;Sharma;Lal, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation